Sistem Pendukung Keputusan untuk Menentukan Mahasiswa Terbaik Menggunakan Metode Complex Proportional Assessment - alwendi; Lela Budiarti; Andi Saputra Mandopa (SMART : Jurnal Teknologi Informasi dan Komputer, 2024)
The aim of this research is to assist the head of the study program in determining the best students each semester. The decision support system is part of a computer-based information system that is used to support decision making in an agency or company. Decision support systems are built to make it easier for someone to make decisions. The system can make a decision according to the considerations that are the criteria in this research, including skills, character, language skills, age, place of residence. The COPRAS method or Combination of Ratio Assessment is a multi-criteria decision analysis method used to overcome complexity and uncertainty in decision making. This method utilizes a ratio approach to evaluate the alternatives involved in a decision. This research aims to obtain ranking results of outstanding students quickly and objectively without requiring a lot of effort. The results of this ranking will help Graha Nusantara Padangsidimpuan University, especially the Faculty of Engineering, Computer Science Study Program, in selecting outstanding students. From the conclusion above, the student selected to be in first place is A3 in the name of indah putri with a score of 99.972 in first place.